The Quaternary plant fossil record from the volcanic Azores Archipelago (Portugal, North Atlantic Ocean): a review. (26th November 2019) - Góis-Marques, Carlos A.; de Nascimento, Lea; Menezes de Sequeira, Miguel; Fernández-Palacios, José María; Madeira, José
Abstract: Plant fossils are known from the Azores Islands, yet poorly studied. We present a comprehensive bibliographical review for the archipelago. A first pre-scientific reference dates from late fifteenth century, while the first scientific description was reported in 1821, accounting for trunks in pyroclastic units and silicified plants within hydrothermal deposits. Throughout the second-half of the nineteenth century and the first-half of the twentieth century, prospection by naturalists and geological mapping work, led to the discovery and description of plant fossils in most islands. From the 1970s onwards, the taxonomic interest ceased, and plant fossils were used mainly for 14 C dating. Recently, sediment cores from lakes and peatlands were used for palaeoecological reconstructions and to measure anthropogenic impacts. Generally, plant fossils are younger than 50 ka, although older fossils may exist. Azorean plant fossils include somatofossils of leaves, stems, logs and seeds preserved as impressions, compressions, adpressions, permineralizations, lava tree casts and mummifications. The taphonomy of macrofloral elements is usually related to explosive volcanic activity, while palynological record is associated with lake sediments and peat bogs. The persistence in palaeobotanical and palaeopalynological studies will decisively contribute to disentangle the paleodiversity, palaeoecology, and add crucial information on insular plant phylogeny and biogeography.